Identification Of Critical Slope Failure Surfaces With Critical Tension Cracks (International Conference on Ground Control in Mining, 1989)
The formation of tension cracks in slopes is well known. Analytical studies require the determination of a critical slip surface for any slope and, in doing so, it is necessary to consider an appropriate tension crack. A general yet simple approach is proposed for identifying the critical slope failure surfaces associated with critical tension cracks. The minimum factor of safety consequently reflects both safety against shear sliding and tensile failure. In general, the critical slope failure surface for a slope determined in this way differs from that which is obtained without optimizing the position and depth of the tension crack. In particular situations, the difference is significant.